Recent improvement of medical optical fibre pressure and temperature sensors - Poeggel, Sven; Duraibabu, Dineshbabu; Kalli, Kyriacos; Leen, Gabriel; Dooly, Gerard; Lewis, Elfed; Kelly, Jimmy; Munroe, Maria (My University, 2015)
This investigation describes a detailed analysis of the fabrication and testing of optical fibre pressure and temperature sensors (OFPTS). The optical sensor of this research is based on an extrinsic Fabry-Perot interferometer (EFPI) with integrated fibre Bragg grating (FBG) for simultaneous pressure and temperature measurements. The sensor is fabricated exclusively in glass and with a small diameter of 0.2 mm, making it suitable for volume-restricted bio-medical applications. Diaphragm shrinking techniques based on polishing, hydrofluoric (HF) acid and femtosecond (FS) laser micro-machining are described and analysed. The presented sensors were examined carefully and demonstrated a pressure sensitivity in the range of sp = 2-10 nm/kPa and a resolution of better than ΔP = 10 Pa (0.1 cm H2O). A static pressure test in 38 cm H2O shows no drift of the sensor in a six-day period. Additionally, a dynamic pressure analysis demonstrated that the OFPTS never exceeded a drift of more than 130 Pa (1.3 cm H2O) in a 12-h measurement, carried out in a cardiovascular simulator. The temperature sensitivity is given by k = 10:7 pm/K, which results in a temperature resolution of better than ΔT = 0.1 K. Since the temperature sensing element is placed close to the pressure sensing element, the pressure sensor is insensitive to temperature changes.
Keywords: Fabry–Perot interferometer; Optical fibre sensors; Pressure sensors